A structural design approach toward metallic glass with simultaneous tunable thermal expansion and high structural stiffness - Yunhao Zhang; Ye Zhou; Conghao Xu; Jiacheng Zhang; Zhendong Sha (Journal of Materials Science: Materials in Engineering)
Abstract Although metallic glasses (MGs) possess relatively low thermal expansion coefficient (α) compared to their crystalline counterparts due to the existence of free volume, their α-values are still too large to meet the demands of practical application. Here, we report that a bi-material structure (BMS) consisting of curved traditional materials (e.g., Al alloy) with MGs can be used to obtain tunable α while maintaining high structural stiffness. The curved Al alloy has a pulling effect on the MGs when the curvature changes, limiting the thermal expansion of MGs. Through the theoretical model and finite element method analysis, it is further found that both α and stiffness can be significantly altered through changing the degree of curvature, the contact surface, and the thickness ratio of MG over Al alloy. The present study not only offers a solution to the α reduction of MGs but also suggests that BMS can be used to design advanced structural materials that possess adjustable α and high stiffness.